Experimental studies of the EuBa2-xEuxCu 3O7- delta compound in the tetragonal phase - Guskos, N.; V. Likodimos; Londos, C.A.; Gamari-Seale, H.; Koufoudakis, A.; Mitros, C.; Niarchos, D. (Journal of Physics: Condensed Matter, 1993)
EPR and magnetic measurements were carried out on specially prepared samples of the EuBa2-xEuxCu3O 7- delta compound in the tetragonal phase, in the temperature range 100-4.2 K. The EPR spectra of Eu2+, Cu2+, coupled pairs of divalent copper ions and the superexchange interaction between Cu ions over oxygen bridges have been observed. The EPR spectrum of europium ions indicates the existence of a crystal-field splitting of the 8S7/2 ground state of Eu2+ ions with a value of the spin-Hamiltonian parameter b20 of about 14*10-2 cm -1. This parameter is analysed within the framework of Newman's superposition model. Anomalies in the temperature variation of the magnetic susceptibility are attributed to the presence of divalent and trivalent europium ions. The susceptibility of Eu3+ ions is non-zero because the excited states are thermally populated and they contribute to the result of the ground state with J=0.